Isolation on a remote island: genetic and morphological differentiation of a cosmopolitan odonate - Alvial, I. E. (2019)
Although low levels of genetic structure are expected in highly widespread species, geographical and/or ecological factors can limit species distributions and promote population structure and morphological differentiation. In order to determine the effects of geographical isolation on population genetic structure and wing morphology, 281 individuals of the cosmopolitan odonate Pantala flavescens were collected from four continental (Central and South America) and five insular sites (Polynesian islands and the Maldives). COI sequences and eight microsatellite loci were used to characterize genetic diversity and genetic structure between and within locations. Linear and geometric morphometry were used to evaluate differences in the size and shape of wings. Genetic analysis showed a global genetic difference between the continental and insular sites. American locations did not show genetic structure, even in locations separated by a distance of 5000 km. Easter Island showed the lowest values of genetic diversity (mainly mitochondrial diversity) and the highest values of genetic differences compared to other insular and continental sites. Individuals from Easter Island showed smaller forewings, a different abdomen length to thorax length ratio, and a different configuration of anal loop in the hindwings. Thus, the greater isolation, smaller area, and young geological age seem to have determined the genetic and morphological differences in P. flavescens of Easter Island, where selection could promote a loss of migratory behavior and may improve other life history traits, such as reproduction. This work provides new insight into how microevolutionary processes operate in isolated populations of cosmopolitan species